Mutational and structural characteristics of four novel heterozygous C‐propeptide mutations in the proα1(I) collagen gene in Chinese osteogenesis imperfecta patients. (12th January 2014) - Lu, Yanqin; Ren, Xiuzhi; Wang, Yanzhou; Li, Tianyou; Li, Fuhui; Wang, Shifu; Xu, Chao; Wu, Guohua; Li, Hu; Li, Gongchao; Zhao, Fei; Wang, Ziqiang; et al.
Summary Objective Osteogenesis imperfecta (OI) with C‐propeptide mutations in proα1(I) collagen gene are rarely reported. We report four novel C‐propeptide mutations in COL1A1 gene from Chinese OI patients. Methods Clinical characteristics and radiographic findings were described for four OI patients with C‐propeptide mutations in proα1(I) collagen gene. Mutations were identified by traditional DNA sequencing based on PCR. The locations of mutations were mapped, and in silico prediction was conducted to analyse their effects on protein structure. Histology studies of skin, bone and muscle tissues were performed. Results All four C‐propeptide heterozygous mutations identified were in the COL1A1 gene. Heterozygous mutation of c.4021C>T (p.Q1341X) disrupted the chain recognition sequences and was found in patients with type IV OI. Mutations of c.3893C>A (p.T1298N) and c.3897C>A (p.C1299X) impeded the formation of disulphide bonds and were associated with type IV OI phenotype. Missense mutation of c.3835A>C (p.N1279H) disrupted Ca2+ binding and led to a severe type III OI phenotype. In silico programs predicted damaging effects for the patients with type III OI and the creation of an exonic splicing enhancer hexamer sequence for the type IV patients. Expansion of the bone marrow cavity and disorganization of osteocyte alignment was evident in bone specimens; and muscle atrophy and enlargement of intramuscular connective tissue were found in muscle specimens. Conclusions Four novel C‐propeptide mutations in proα1(I) collagen gene were identified in Chinese OI patients, and their clinical severity ranged from moderate type IV to severe type III. In silico prediction of the mutation effect and histological characteristics of tissue specimens was in accordance with the OI phenotypes.